A numerical simulation for reduction of rudder cavitation with gap flow blocking bars - Jungkeun Oh (International Journal of Naval Architecture and Ocean Engineering, 2012)
In recent practices, a half circular prismatic bar protruding beyond the concave surface of the horn facing the gap has been formed along the centerplane of a rudder to lessen the gap flow between the horn and the movable portion of the rudder system. If a flow through the gap of a rudder is reduced considerably through this approach, previous numerical studies indicate that not only the gap flow but also the rudder cavitation can be noticeably diminished. In the present study, numerical simulations on two-dimensional rudder sections were performed to show that the blocking ability of the single centre bar can be improved by the proper choice of sectional shape. Moreover, a pair of blocking bars attached symmetric to the centerplane on the opposite convex surface of the movable portion is suggested in the study as well, to circumvent the difficulties arising from the practical application of the single centre bars. The bars are placed near the outer edges of the gap easily accessible at the maximum rudder angle to allow simple installation of the device during a maintenance period of a ship. It is found that the pair of blocking bars further improves the blocking effects and application to a practical three-dimensional rudder also backs up the fact.